DEVELOPMENT OF URBAN SLUMS THROUGH ALTERNATE VERTICAL LAND CONSOLIDATION MODELS - Nur Khoirinnisa, Nadya
West Java is a province with the highest population density in Indonesia. 48 million people or 18.34% of the total population live in there. The high rate of urbanization is the biggest contributor to the growth of population density which has led to the emergence of slums. Slums that tend to spread irregularly make urban spatial structure worse. The solution of this problem is by rearranging slum areas through vertical consolidation of land (KT) in the form of flat. Based on data from The Spatial Palnning and Ciptakarya Agency in Bandung, there are 29 urban villages that are categorized as high slums. One of them is Babakan Surabaya. There are 15 hamlets (RW) in Babakan Surabaya and the research location is at RW 09, based on AHP calculation. Participatory Rural Appraisal (PRA) method is used as the research method. PRA is a participatory activity and the community is encouraged to gather information about the problem. There are several analysis used, including a) gap analysis, showing that the research area does not fit the criteria of a decent settlement; b) descriptive analysis, showing that only about 24% of the people agreed to the concept; c) SWOT analysis is used to see the slum development model through vertical KT, resulting in vertical KT model 1 is suitable to be applied in the research area; and d) analysis of development financing generates sales values for commercial, shop, and retail flats of the two vertical KT models, which the value of vertical KT models 1 of Rp 167,494,368,326, and vertical KT models 2 of Rp 140,290,832,571.